2008
DOI: 10.1111/j.1600-051x.2008.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 7, Epstein–Barr virus and human cytomegalovirus in periodontal tissues of periodontally diseased and healthy subjects

Abstract: The results indicate that (i) gingival tissues can be considered a potential reservoir for HHV-7; (ii) when present, HHV-7 persists in a latent state in the majority of cases; (iii) the presence of EBV seems to be associated with the diseased state of the patient and site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 42 publications
4
75
2
2
Order By: Relevance
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010. 2 In his study, we noted that a co-infection of HCMV and EBV existed in CP group and this relationship was significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the genotype distribution and seroprevalence of EBV and HCMV differ among populations [8,13]. Additionally, molecular studies have directly compared the endodontic microbiota of patients from different geographic locations and found significant differences in the prevalence of some important species [3,14].…”
Section: Research Articlementioning
confidence: 99%
“…5 The prevalence of herpes simplex virus type I (HSV-1) and Epstein-Barr virus (EBV) is reported to be associated with periodontitis and PI. 6,7 However, the pathogenetical mechanisms are still not clearly understood. 8 The prevalence of herpes viruses is extremely high and…”
Section: Introductionmentioning
confidence: 99%